Pengaruh Sisa Amelioran, Pupuk N dan P terhadap Ketersediaan N, Pertumbuhan dan Hasil Tanaman Padi di Musim Tanam Kedua pada Tanah Gambut - Kurniawan Subatra (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
The objective of this research was to know the residual effect of Ameliorant and N, P-fertilizer on availability of nitrogen, growth, and rice yield on the second of season planting on peat soil. This research was conducted from May 2006 until September 2006 at Green House of Soil Department of Agriculture Faculty, Sriwijaya University. This research use Randomized Completely Block Factorial Design with three factors of treatment and three applications. First treatment was two dosages (0 and 5 ton/ha) of ameliorant that was consist of organic manure and dolomite and the second and third was three dosages (0, 50, 100 kg/ha) of N and P-fertilizer. Result of experiment showed that ameliorant, N and P-fertilizer with their combination have given significant effect on availability of nitrogen, but haven’t given significant effect on growth and rice yield on the second season cropping on peat soil.